Gluten-free foods F.G. Roberts producing food for a niche Market - Leigh, Richard; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2000)
Outlines the unique properties of gluten, its special elasticity and hence its pivotal role as a raising agent in baking, especially bread. Also discusses gluten allergies and the development of gluten-free bread flour for coeliac disease patients
Executive producer, Stephen Skok ; editor, Rowena Crowe
DVD format
Keywords: Gluten; Gluten -- Health aspects; Food allergy; Celiac disease